2008
DOI: 10.1016/j.eurpsy.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the WHO depression guideline on patient care by psychiatrists: A randomized controlled trial

Abstract: The results show both positive and negative effects of guideline exposure, but only in the training group and not in the information group. Guidelines should be empirically tested before being called "evidence based". Every guideline should also explain how it can or must be implemented in order to become effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…In order to achieve these changes, an active implementation was needed and not just a dissemination of, or lecturing about, guidelines. This finding is in accord with earlier studies [11,29,30]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In order to achieve these changes, an active implementation was needed and not just a dissemination of, or lecturing about, guidelines. This finding is in accord with earlier studies [11,29,30]. …”
Section: Discussionsupporting
confidence: 94%
“…Guidelines aim to influence the treatment behaviour of practitioners. However, studies are needed to show that physicians exposed to guidelines provide better treatment [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies included 239,477 patients, with one study (Eccles et al, 2007) not reporting the number of patients. The total number of sites was 378, ranging from 1 to 73 per study, with five studies not reporting the number of sites (Worrall et al, 1999;Azocar et al, 2003;Gerrity et al, 1999;Linden et al, 2008;Shirazi et al, 2013). Six studies did not report any information about a power calculation, nine studies reported an a priori power calculation with targeted sample size achieved, and seven noted a post hoc analysis indicating insufficient power.…”
Section: Designmentioning
confidence: 99%
“…Twenty studies took place in primary care settings, ranging from primary care offices and academically affiliated primary care practices to family medicine research network practices and continuing medical education groups. Two studies took place in specialty care settings: a private psychiatry practice (Linden et al, 2008) and a managed behavioral health care organization (Azocar et al, 2003). Specific names of the sites as described in the articles can be found in Appendix C.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation